1999
DOI: 10.3141/1675-01
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Soft Swiss Lacustrine Clay: Cone Penetration and Triaxial Test Data

Abstract: A new link road is to be constructed top down between parallel cast-in place pile walls under a series of railway lines in Kreuzlingen, Canton Thurgau, which is an important hub in the regional transportation network. The results of a site investigation on the soft, normally consolidated, post-glacial lacustrine clay deposit underlying the railway lines, including a cone penetration test, undisturbed sampling from an adjacent borehole, and laboratory testing, are reported. Strength characteristics of the clay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…It is higher than might be expected on the basis on previously suggested range of values, although a sensitivity of 3 to 5 may be partially responsible. Springman et al (1999) suggested a linear trend for a characteristic undrained shear strength s u for Kreuzlingen clay that was supported by triaxial stress path data as well in compression and extension (see Fig. 2).…”
Section: Mechanical Characterisation Of Clays By Cptu Interpretationmentioning
confidence: 77%
See 4 more Smart Citations
“…It is higher than might be expected on the basis on previously suggested range of values, although a sensitivity of 3 to 5 may be partially responsible. Springman et al (1999) suggested a linear trend for a characteristic undrained shear strength s u for Kreuzlingen clay that was supported by triaxial stress path data as well in compression and extension (see Fig. 2).…”
Section: Mechanical Characterisation Of Clays By Cptu Interpretationmentioning
confidence: 77%
“…(8) Figure 8 reports the trend functions calculated by this study on the A201 s u profile at the Wauwil Springman et al (1999). site and the one derived from Springman et al (1999) at Kreutzlingen.…”
Section: Trend Function and Spatial Variabilitymentioning
confidence: 99%
See 3 more Smart Citations